PROBLEM-BASED LEARNING AS A METHOD TO IMPROVE SENIOR HIGH SCHOOL STUDENT’S READING COMPREHENSION IN ENGLISH - Husnur Rosyidah Aulia; Anita Fatimatul Laeli; Siti Ulwiyah (ELTR Journal, 2023)
In the current curriculum in Indonesia where it aimed to be more student-centered, the implementation of Problem-Based Learning is heavily reinforced. This is because how Problem-Based Learning is not just about being student-centered, but also because it encourages students to be problem solvers and learn through their understanding. This paper aims to see how Problem-Based Learning can affect the students’ reading comprehension in class. Classroom Action Research is chosen in this study. The participants were 30 students of the Senior High School English classes in Ambulu. Based on the findings, the Problem-Based Learning method could potentially become an effective method for students as there is a significant change between the first cycle and the second cycle of the use Problem- Based Learning method in the class. The improvement shown is that almost all of the students had their scores improved in the reading comprehension test after the implementation of Problem-Based Learning.